Use of Financial Ratios in Identifying Jet Airways’ Financial Distress - Rengaswamy, Vasudevan (Digital Repository of Theses, 2024)
The aviation sector is a crucial contributor to GDP. Jet Airways, a prominent airline in India, is currently facing significant financial distress, necessitating a thorough examination to support its ongoing contribution to the country's economy and overall growth. The research questions are: What causes financial distress for Jet Airways? How should the airline use the financial process ratio to analyze to come out of financial distress? How can financial ratios help forecast the debt crisis? This study is significant because the financial ratio estimates will help identify financial distress at Jet Airways, thus providing fairness and returns to both investors and creditors of this company. The study uses liquid asset theory and liquidity and profitability theories. In addition, the study employs a mixed research design based on qualitative and quantitative analysis of data from Jet Airways’ financial statements. The findings of this study reveal that Jet Airways' financial distress originated from severe financial difficulties due to a combination of factors, including high fuel prices, a depreciating Indian rupee, intense competition, and rising debt levels. Furthermore, empirical analysis results obtained through Altman’s Z-score and logistic regression models revealed that financial ratios that are categorized as profitability and liquidity are significant predictors of financial distress for Jet Airways. Consequently, for the airline to avoid future bankruptcy, it must implement an effective debt management plan and adopt robust cost reduction measures.